Hak Konstitusional Bagi Penyandang Disabilitas Mental Dalam Pemilihan Umum - Rasyid Rahmat; Sodikin Sodikin (STAATSRECHT: Indonesian Constitutional Law Journal, 2018)
This study aims to determine the position of persons with mental disabilities legally and the limitations of their constitutional rights in elections. People with mental disabilities are another term for people in mental disorders. This research is a normative legal research using the statutory approach to understand the concept of the position of persons with mental disabilities in elections as regulated in legislation that is intended as an effort to bring the problem under study according to the rules, norms, and rules in accordance with the object of study. The results showed that the granting of the right to vote for people with mental disabilities to realize the ideals of the Indonesian people is a democracy based on equal rights, as well as the concept of democracy that prioritizes the principle of one man, one vote, one value, so that they are sick and treated at home mentally ill have the right to vote even though the granting of the right to vote does not provide legal certainty, even injuring the sovereignty of the people themselves.